Cervical cancer in Nepal: Current screening strategies and challenges - Narasimhamurthy, Mohan; Kafle, Santhosh Upadhyaya (Frontiers in Public Health, 2022)
Nepal has a high burden of cervical cancer primarily due to a limited screening program. Most present with advanced cervical disease. Despite no national cervical cancer control program, Nepal's Ministry of Health and Population has taken many initiatives with various international collaborations in screening, vaccination, and treating pre-invasive and invasive cancer. However, the existing prevention and treatment modalities are dismally inadequate to meet the targets of WHO's cervical cancer eliminative initiative by 2030. We provide an overview of the Ministry of Health and Population, Nepal's efforts to tackle the growing cervical cancer burden in the country. We discuss the challenges and potential solutions that could be practical and augment screening uptakes, such as single-dose vaccination and HPV DNA tests. The screen-and-treat approach on the same day could potentially address treatment delays and follow-up loss after testing positive. Our narrative summary highlights existing and innovative strategies, unmet needs, and collaborations required to achieve elimination across implementation contexts.